Internal Carbon Pricing and Climate Performance: Evidence and Implications for Disclosure Standards - Alves, T.; Bento, N.; Ghitti, M.; Gianfrate, G. (SSRN, 2025)
Internal carbon pricing (ICP) is a widespread practice adopted by global companies to factor transition climate risks in strategic and operational decisions. Policymakers and standard setters are issuing guidelines for companies to disclose their ICP, under the assumption that disclosing such element to firm stakeholders would enable a more virtuous transition towards low carbon production. However, the assumption that ICP disclosure can effectively foster the reduction of carbon footprint remains untested. This paper examines the use of ICP among firms reporting to the Carbon Disclosure Project (CDP) focusing on the 2016 survey in which companies were asked to disclose not only the ICP adoption but also whether carbon prices had been already used in decision-making, and whether they were integrated into operational targets. Analyzing emissions data through 2022, we find that disclosure alone and reported past use of ICPs do not predict subsequent reductions in carbon intensity. Only firms that integrate ICPs into operational targets show significant emissions cuts. These findings underscore the limits of disclosure alone as proposed by some standard setters and suggest the elements that should inform the design of disclosure frameworks for climate accounting metrics.